Analisis Bentuk Interaksi Sosial pada Pembelajaran Outdoor di Sekolah Dasar - Nursyamsi, Nursyamsi; Wiratman, Arwan; Jayanti, Nayunda Dwi (Institut Agama Islam Daruttaqwa Gresik, 2024)
This study aims to analyze the form of social interaction between students and students in outdoor learning at State Elementary School 11 Dangerakko to find out the form of social interaction between students and teachers in outdoor learning at Sekolah SD Negeri 11 Dangerakko to find out the supporting factors of social interaction between students and teachers with students in outdoor learning at State Elementary School 11 Dangerakko. This research will be carried out in 2023, with the subject being students of S.D.N. 11 Dangerakko. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and verification. This study shows that the analysis of student interaction with students in outdoor learning is very good, and student interaction with teachers is very good and smooth.